Diagnostic values of edema-sensitive T2-weighted imaging, TSE T1-weighted early contrast-enhanced imaging, late gadolinium enhancement, and the Lake Louise criteria in assessing acute myocarditis: A single-center cardiac magnetic resonance study - Deniz Alis; Arda Güler; Ozan Aşmakutlu; Begüm Uygur; Seyhan Ördekçi (KARE Publishing, 2020)
Objective: The aim of this study was to evaluate the diagnostic accuracy of the Lake Louise consensus criteria using cardiac magnetic resonance (CMR) imaging assessment of edema, hyperemia, and late gadolinium enhancement (LGE) in the diagnostic determination of acute myocarditis. Methods: A total of 44 patients with acute myocarditis and 24 healthy controls were included in this retrospective study. The presence of edema was defined as a myocardial mean signal intensity >1.9 times that of the skeletal muscle in the same slice on T2-weighted short tau inversion-recovery sequences. Hyperemia was defined as an early gadolinium enhancement ratio (EGEr) ≥4 calculated using the contrast-enhancement of the myocardium and skeletal muscle on TSE T1-weighted sequences, and LGE was assessed by visual examination. The reference methods used to determine the presence of myocarditis were based on the European Society of Cardiology Working Group on Myocardial and Pericardial Diseases guidelines for clinical and biochemical findings. Results: The diagnostic accuracy of edema, hyperemia, LGE, and the Lake Louise criteria (at least 2 of 3 components) was 75.7%, 64.2%, 88.5%, and 84.2%, respectively. Among the 3 components of the Lake Louise criteria, edema had the highest specificity (100%), and LGE had the highest sensitivity (86%). The use of LGE and/or edema as a criterion for acute myocarditis revealed the highest diagnostic accuracy (92.8%) among the CMR sequences and combinations of components examined. Conclusion: LGE and/or edema as a sole criterion for the diagnosis of acute myocarditis demonstrated better diagnostic accuracy than the Lake Louise criteria. The use of EGEr did not improve the performance of CMR-based diagnosis. Alternatives to the use of EGEr are recommended for the diagnosis of acute myocarditis.